2023
DOI: 10.1007/s11010-023-04674-7
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta 1 (TGF-β1) in COVID-19 patients: relation to platelets and association with the disease outcome

Abstract: Transforming growth factor beta (TGF- β ) is a ubiquitously distributed cytokine known to contribute to the pathogenesis of numerous pathological processes. The aim of this study was to measure serum concentrations of TGF- β 1 in severely ill COVID-19 patients and to analyze its relationship with selected hematological and biochemical parameters and with the disease outcome. The study population included 53 COVID-19 patients with severe clinical expression of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…On the other hand, Karadeniz et al, in their cross-sectional study, showed no significant difference in TGF-β1 concentrations between 59 COVID-19 patients and 30 healthy controls [ 27 ]. Recently, Zivancevic-Simonovic S et al showed that lower serum TGF-β1 concentrations were associated with unfavorable outcomes in severe COVID-19 [ 43 ]. In patients with long COVID who developed pulmonary fibrosis, TGF-β1 was elevated [ 44 ], which is not unusual considering that TGF-β is one of the main promoters of fibrosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Karadeniz et al, in their cross-sectional study, showed no significant difference in TGF-β1 concentrations between 59 COVID-19 patients and 30 healthy controls [ 27 ]. Recently, Zivancevic-Simonovic S et al showed that lower serum TGF-β1 concentrations were associated with unfavorable outcomes in severe COVID-19 [ 43 ]. In patients with long COVID who developed pulmonary fibrosis, TGF-β1 was elevated [ 44 ], which is not unusual considering that TGF-β is one of the main promoters of fibrosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they observed differences in TGF-β concentration between COVID-19 subjects dependent on the total platelet (PLT) count in their blood, indicating that the higher the platelet count is, the greater the TGF-β concentration. Interestingly, COVID-19 patients with a normal PLT count did not differ from heathy controls in terms of TGF-β levels [22]. In our study, we were assessing TGF-β in mild-to-moderate COVID-19 convalescents, at least 6 months after recovery.…”
Section: Discussionmentioning
confidence: 69%
“…TGF-β1 in uences immune cell development, differentiation, tolerance induction, and homeostasis, with pleiotropic effects contributing to either immune response or tolerance establishment. While previous research has implicated TGF-β1 in various pathological processes, its role in COVID-19 progression and outcome remains inadequately explored [30].…”
Section: Resultsmentioning
confidence: 99%
“…To examine the daily change of TGF-β1 level in other planned studies, It may be useful to explain changes in the pathogenesis of the disease. Snezana Zivancevic-Simonovic and her colleagues [30] discovered that the concentration of TGF-β1 was lower in individuals who succumbed to COVID-19 compared to those who survived. Furthermore, their correlation analysis revealed a robust positive connection between TGF-β1 levels in patients' serum and platelet counts.…”
Section: Resultsmentioning
confidence: 99%